Mais que me chantez-vous là ? Abus de langue et abus de langage - Laetitia Pille (Corela)
Often the tongues the languages and the language CAN be confused to the benefit of a simplified analogy being associated to music as a tongue. We are often told that music is a tongue or a language anyway or just the language of music. This article not only aims at revealing some reasons to explain false analogies but also at distinguishing better the tongues the languages and the language. Throughout this discriminating study we present and face the theory of linguists, of philosophers, of scientists of cognition and of musicologists. The semantic of point of view presented by Pierre-Yves Raccah gave references to which the other theories are up against. Beyond the simple differences of definition and of description we have brought up to date the ideologies revealed by these same definitions or descriptions of music where it is described as a tongue or a language.